Clinically Actionable Genotypes Among 10, 000 Patients With Preemptive Pharmacogenomic Testing. Issue 4 (19th November 2013) - Van Driest, SL; Shi, Y; Bowton, EA; Schildcrout, JS; Peterson, JF; Pulley, J; Denny, JC; Roden, DM
<x xml:space="preserve">Abstract</x> Since September 2010, more than 10, 000 patients have undergone preemptive, panel‐based pharmacogenomic testing through the Vanderbilt Pharmacogenomic Resource for Enhanced Decisions in Care and Treatment program. Analysis of the genetic data from the first 9, 589 individuals reveals that the frequency of genetic variants is concordant with published allele frequencies. Based on five currently implemented drug–gene interactions, the multiplexed test identified one or more actionable variants in 91% of the genotyped patients and in 96% of African American patients. Using medication exposure data from electronic medical records, we compared a theoretical "reactive, " prescription‐triggered, serial single‐gene testing strategy with our preemptive, multiplexed genotyping approach. Reactive genotyping would have generated 14, 656 genetic tests. These data highlight three advantages of preemptive genotyping: (i) the vast majority of patients carry at least one pharmacogenetic variant; (ii) data are available at the point of care; and (iii) there is a substantial reduction in testing burden compared with a reactive strategy. Clinical Pharmacology & Therapeutics (2014); 95 4, 423–431. doi:10.1038/clpt.2013.229